Salivary Gland. Photon beam and particle radiotherapy: Present and future. (September 2016) - Orlandi, Ester; Iacovelli, Nicola Alessandro; Bonora, Maria; Cavallo, Anna; Fossati, Piero
Highlights: Advanced RT technique are promising in SGCs treatment. Based on retrospective data PORT is recommended in high risk SGCs patients. Particle therapy should be the first option for inoperable or R2-resected SGCs. Abstract: Salivary gland cancers (SGCs) are rare diseases and their treatment depends upon histology, stage and site of origin. Radical surgery is the mainstay of treatment but radiotherapy (RT) plays a key role in both the postoperative and the inoperable setting, as well as in recurrent disease. In the absence of prospective randomized trials, a wide retrospective literature suggests postoperative RT (PORT) in patients with high risk pathological features. SGCs, and adenoid cystic carcinoma (ACC) in particular, are known to be radio-resistant tumors and should therefore respond well to particle beam therapy. Recently, excellent outcome has been reported with radical carbon ion RT (CIRT) in particular for ACC. Both modern photon- and hadron-based treatments are effective and are characterized by a favourable toxicity profile. But it is not clear whether one modality is superior to the other for disease control, due to the differences in patients' selection, techniques, fractionation schedules and outcome measurements among clinical experiences. In this paper, we review the role of photon and particle RT for malignant SGCs, discussing the difference between modalities in terms of biological and technical characteristics. RT dose and target volumes for different histologies (ACC versus non-ACC) have also been taken into consideration.